Time and Frequency Activities at the U.S. Naval Observatory. (22nd July 2008) - Matsakis, Demetrios
Abstract : The US Naval Observatory (USNO) has provided timing for the navy since 1830 and, in cooperation with other institutions, has also provided timing for the United States and the international community. Its Master Clock (MC) is the source of UTC(USNO), the USNO's realization of Coordinated Universal Time (UTC), which has stayed within 5 nanoseconds RMS of UTC since 1999. The data used to generate UTC(USNO) are based upon 73 cesium and 21 hydrogen maser frequency standards in three buildings at two sites. The USNO disseminates time via voice, telephone modem, LORAN, Network Time Protocol (NTP), GPS, and two-way satellite time transfer (TWSTT). This paper describes some of the changes being made to meet the future needs for precision, accuracy, and robustness.